Effects of force- and velocity-oriented conditioning activities on jump height in strength-deficient male participants - Koźlenia, Dawid; Kozinc, Žiga; Garcia-Ramos, Amador; Domaradzki, Jarosław (Frontiers in Physiology, 2025)
IntroductionVarious factors are known to influence the effectiveness of post-activation performance enhancement (PAPE) protocols. However, whether individual’s force–velocity (FV) profile affects the impact of conditioning activity (CA) remains unclear. This study examined whether PAPE is influenced by addressing individual strength deficits, identified through FV profiling, using either force- or velocity-oriented conditioning. Specifically, we (i) assessed the effectiveness of force-oriented (PAPE-F) and velocity-oriented (PAPE-V) protocols on acute jump height (JH) performance in individuals with strength deficits and (ii) investigated whether the magnitude of force–velocity imbalance (FVimb) is significantly associated with PAPE in JH.MethodsTwenty-five young (19–27 years), resistance-trained male individuals (≥2 years of continuous training) who exhibited a strength deficit, determined by FVimb in the squat jump (SJ), were included in this study. They performed either three sets of five assisted jumps (PAPE-V; load reduced by 30% of body mass) or three four-second sets of maximal isometric contractions (PAPE-F), each with 1 min rest intervals. JH was measured at baseline and 3, 6, and 9 min post-CA.ResultsA three-way (group × condition × time) repeated measures ANOVA revealed significant effects of time (F = 7.78; partial-η2 = 0.14; p < 0.01) and a significant condition × time interaction (F = 16.57; partial-η2 = 0.26; p < 0.01) for JH. The Bonferroni post hoc test revealed significant within-group improvements after PAPE-F at the 6th min (p < 0.01; ES = 0.32) and 9th min (p < 0.01; ES = 0.33) compared to baseline and after PAPE-V at the 3rd min (p < 0.01; ES = 0.24), 6th min (p < 0.01; ES = 0.36), and 9th min (p < 0.01; ES = 0.30) compared to baseline. Linear regression models showed that individuals with lower FVimb exhibited greater PAPE effects following the PAPE-F protocol (β = 0.63; R2 = 40; p = 0.03), but no significant associations were observed between these two variables for the PAPE-V protocol (R2 = 0.19; p = 0.53).DiscussionThese results suggest that individuals can achieve comparable acute JH improvements using force- or velocity-oriented CAs, although force-oriented CA may promote greater gains in individuals with lower FVimb.